The Automatic Monitoring System for WPP, SPP, and PLN based on The Internet of Things (IoT) using Sonoff Pow R2 - Yosi Apriani; Muhammad Rama Bagaskara; Ian Mochamad Sofian; Wiwin A Oktaviani; Muhammad Hurairoh (Elinvo (Electronics, Informatics, and Vocational Education), 2021)
The usefulness of monitoring systems in the electric power system supports the importance of people's work today. One of which is the monitoring system at the generator. The monitoring system for Wind Power Plant (WPP), Solar Power Plant (SPP), and electricity from State Electricity Company (PLN) use IoT (Internet of Things) in the form of Sonoff Pow R2. With the monitoring system on this tool, the parameter values for WPP, SPP, and PLN can be seen and monitored online via a smartphone. The purpose of this research is to design a monitoring system for WPP, SPP, and PLN based on the Internet of Things (IoT) to determine the value of the output power. In addition, this system can distinguish load parameter values when WPP, SPP, and PLN are supplied directly (real time) and monitored online using the Sonoff Pow R2 app and the Ewelink App. This study uses the methodology that started the process of designing and manufacturing systems and designing the wiring that has been formed from the process of making tools and testing results. The results obtained from the experiment show that the current values in WPP, SPP, and PLN that appear on the monitoring screen are stable.  The stable condition values are measured and tested when power is used when loading through sonoff.  For the power value, the power value in PLN is stable, whereas in WPP and SPP has increased. For the voltage, the voltage value from PLN does not reach 220 V, whereas the voltage value from WPP and SPP reaches a value of 220 V.